Medical Tourism - Connell, John (CABI, 2014)
Medical tourism, where patients travel overseas for operations and various invasive therapies, has grown rapidly since the late 1990s, especially for cosmetic surgery. The main sources of such tourists are developed countries and the main destinations are in Asia. Conventional tourism has been a by-product of this growth, despite its tourist packaging, but the overall beneﬁ ts to the tourism industry have been considerable. The rise of medical tourism empha- sizes a number of contemporary themes including the privatization of health care in post- industrial economies, the growing dependence on technology, uneven access to health resources, the accelerated globalization of health care and tourism, rampant consumerism and cherishing the body beautiful. One of the more intriguing changes of the past two decades has been a remarkable focus, even obsession, with bodily appearance. Both health and its visible signs have become more and more important. Day after day as I open my e-mails, I am told that I need to take pills, exercise or modify my appearance – usually one particular part of my anatomy. I am encour- aged to have a hair transplant, take viagra, ordered to ‘lose weight fast without exercising’ and generally made to feel inadequate. As I was writing this Preface two new e-mails appeared on my computer screen entitled ‘Your manly strength and stamina will be restored again’ and ‘look great and speed up your metabolism with Acai berry’. They keep coming because people keep responding, as so many want to ‘look great’. Businesses have sprung up around inade- quacy. Yet, fortuitously, my own lone foray into medical tourism was an hour of dental treat- ment in Bangkok that cost barely one-ﬁ fth of the equivalent in Sydney. No longer is plastic surgery to be frowned upon or merely for the elite, while looking good has become an obses- sion. Indeed cosmetic surgery is ﬁ rmly engrained in popular culture; Stieg Larsson’s feminist heroine of The Girl Who Played With Fire (2009) engaged in breast enhancement, while Robin Cook’s series of medical thrillers turned to medical tourism a year earlier with his Foreign Body (2008), centred around an American’s hip replacement in India.